Early plasma protein and mineral changes after surgery: a two stage process. Issue 8 (August 1984) - Myers, M A; Fleck, A; Sampson, B; Colley, C M; Bent, J; Hall, G
Abstract : Sequential changes in albumin, transferrin, alpha 1-acid glycoprotein, C reactive protein, fibrinogen, copper, iron, and zinc in plasma up to 24 h after hysterectomy were measured. No increases in the concentrations of the acute phase proteins alpha 1-acid glycoprotein, C reactive protein, and fibrinogen were observed until 6 h after the skin incision. These increases were preceded by significant falls at 2-4 h, and this was shown also by albumin, transferrin, iron, zinc, and copper. The ratios of iron and zinc to their binding proteins, transferrin and albumin, did not decrease until 4-6 h and their concentrations remained low for at least 24 h. These patterns suggest that at least two mechanisms operate after trauma. The early fall in the concentrations of the proteins in plasma is consistent with a prompt increase in microvascular permeability. The later decrease in binding of the metals iron and zinc to their transport proteins and the increase in concentrations of the acute phase proteins could be initiated by a common mediator.